Original paper Thoracoscopic splanchnicectomy in chronic epigastric visceral pain therapy - Kordiak, Jacek; Brocki, Marian; Rysz, Jacek; Stolarek, Robert; Santorek-Strumiłło, Edyta J.; Gruda, Robert; Jabłoński, Edward (Archives of Medical Science, 2005)
Background: The rapid development of minimal invasive surgery in the 1990s coincided with the introduction of videothoracoscopic splanchnicectomy of nerve fibers engaged in the sensation of chronic pain related with advanced cancer. This study was aimed to determine pain intensity in patients with advanced cancer in the epigastric region before and after thoracoscopic splanchnicectomy. Material and methods: The thoracoscopic splanchnicectomy was performed in 33 patients aged 42 to 77 form 2001 to 2005. Patients with chronic epigastric pain due to advanced cancer were qualified for the surgery. The pain intensity was ranked with Prince Henry Hospital Pain Scale (PHHPS). Results: Even though all study patients were on continuous analgesic medications, the mean pain intensity in PHHPS scale was 2.67 points. Two days and thirty days after the surgery, the pain was ranked 1.28 and 1.57, respectively. All patients decreased the doses of their analgesic medication and seven of them entirely discontinued analgesic therapy. Conclusions: The thoracoscopic splanchnicectomy is well suited, although relatively little known, method of the therapy of chronic pain in advanced malignancy. It may be recommended as an option in the current palliative analgesic therapy.